Mid- to Late Cambrian docking of the Río de la Plata craton to southwestern Gondwana: Age constraints from U-Pb SHRIMP detrital zircon ages from Sierras de Ambato and Velasco (Sierras Pampeanas, Argentina) - Verdecchia, Sebastián Osvaldo (2011)
The Early Palaeozoic stratigraphy and tectonic history of the Eastern Sierras Pampeanas of central Argentina are complicated by metamorphism and deformation resulting from the Pampean (545-510 Ma) and Famatinian (490-440 Ma) orogenies. We report U-Pb sensitive high-resolution ion microprobe dating of detrital zircons in two metasedimentary successions exposed at Quebrada de La Cébila (c. 28°45'S, 66°25'W): the Ambato and the La Cébila metamorphic complexes. The Ambato zircons record age peaks corresponding to Pampean (530 ± 10 Ma), Brasiliano (c. 570 and c. 640 Ma), Grenville (c. 950 to c. 1025 Ma) and minor Neoarchaean ages. Similar peaks are also apparent in the La Cébila sample but it additionally contains Palaeoproterozoic zircons (c. 2.1 Ga) corresponding to the age of the Rio de la Plata craton, from which they are considered to have been sourced. Our interpretation is that the protolith of the Ambato complex was deposited prior to juxtaposition with the craton and is older than the Early Ordovician La Cébila metamorphic complex. We infer that the craton reached its current relative position in the Mid- to Late Cambrian, after the main Pampean tectonothermal event (530-520 Ma) and before deposition of the La Cébila protolith and the Achavil Formation (Sierra de Famatina), which contain comparable detrital zircon populations.